2014
DOI: 10.4103/0301-4738.136204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistive index using color Doppler imaging of orbital arteries in geriatric patients with hypertension

Abstract: Background and Aim:Resistive index (RI) is an indirect measurement of blood flow resistance that can be used to evaluate vascular damage in ophthalmologic disease. The purpose of this study was to evaluate the association between RI values of orbital arteries using the color Doppler imaging (CDI) in geriatric hypertensive patients with or without retinopathy.Setting and Design:Designed as a cross-sectional study.Materials and Methods:We evaluated 60 geriatric patients with hypertension (Group 1) and 30 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
2
8
3
Order By: Relevance
“…As an affirming finding, Karadeniz-Bilgili et al 5 found increased RI values in hypertensive patients compared to healthy subjects. Akal et al 11 found a higher RI of PCA levels and similar OA and CRA levels in geriatric hypertensive patients compared to healthy subjects. The RI of the orbital arteries in hypertensive patients with or without retinopathy has not yet been investigated and compared.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As an affirming finding, Karadeniz-Bilgili et al 5 found increased RI values in hypertensive patients compared to healthy subjects. Akal et al 11 found a higher RI of PCA levels and similar OA and CRA levels in geriatric hypertensive patients compared to healthy subjects. The RI of the orbital arteries in hypertensive patients with or without retinopathy has not yet been investigated and compared.…”
Section: Resultsmentioning
confidence: 94%
“…healthy controls (Tables 1 and 2). Akal et al 11 evaluated RI values of OA, CRA, and PCA in patients with hypertensive retinopathy and found no significant difference compared to patients without hypertensive retinopathy.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with hypertension, the RI of the PCA is reported to be high and correlates with duration of hypertension. [ 18 ] Moreover, CDI was performed in erect posture, which might have influenced the results. Few other investigators have noted increased RI values in the OA and CRA in patients with diabetes but without DR compared to that of controls, suggesting that even before the appearance of overt DR, there is increased resistance to blood flow in the peripheral vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…CDI is a useful method to investigate ocular and orbital blood flow characteristics (Aburn and Sergott 1993;Munk et al 1993;Rojanapongpun and Drance 1993;Baxter et al 1995;Dudea 2011) that has been successfully applied in clinical settings for the evaluation of the circulatory status in retinal vascular disorders and glaucoma (Williamson and Harris 1996;Rankin 1999;MacKinnon et al 2000;Akal et al 2014). The topography and direction of the blood flow in many ocular and retro-orbital vessels, such as the external and internal ophthalmic artery, anterior ciliary artery, short and long ciliary arteries and primary retinal artery, have been described clearly in dogs (Gelatt-Nicholson et al 1999a;Lee et al 2002;Novellas et al 2007).…”
Section: Discussionmentioning
confidence: 99%